TURKMENISTAN: CURRENT POLITICS - Proklov, Igor (CENTRAL ASIA AND THE CAUCASUS, 2008)
Late in December 2006, President Niyazov, who had been in power for over twenty years, suddenly died. This death defrosted the political process driven to a standstill by the advent of the Golden Age in Turkmenistan and kindled hopes of positive developments both inside and outside the country: indeed, death was the only thing that could end Turkmenbashi’s unlimited rule. During his lifetime the expert and political communities agreed that under Niyazov the country was well protected against a Color Revolution (which cannot be said about its CIS neighbors). No Color Revolution shook the republic after his death either. Today Turkmenistan is sending positive signals to the world: opera and circus have returned to the country of barchans and camels; the country’s leaders restored the nation’s favorite holidays, International Women’s Day (8 March) and Victory Day (9 May), and annulled the former president’s birthday (19 February) as a national holiday. These were the initiatives of the new president, Gurbanguly Berdymukhammedov, who in February 2008 marked his first anniversary in power. This short period has brought numerous changes for the better: the local people agree that life has become easier, there are fewer limitations, and much more freedom. There is talk about a “thaw” after the long period of Niyazov's authoritarian and cruel rule. It is no surprise that the term and positive changes bring to mind the Soviet past associated with Nikita Khrushchev: the image of the late president was desacralized, people no longer pledge loyalty to the president every day (this ritual is reserved for official events), the nation is no longer obliged to study Rukhnama, the moral code of the Turkmens. Will the trend continue? Which direction will be chosen for the political process? While the president was still alive, political scientists and the ordinary people asked themselves what would happen to the country after his death. Having become an authoritarian leader with no contenders or opposition on the political field, he (very much like Stalin before him) gave little thought to a potential successor and to his country’s life after his death. Despite the unending stream of wishes of “many happy returns of the day” and good health coupled with the lavishly paid services of the best Western cardiologists, his heart failed. This death put an end to a cruel and tragic period in the country’s history, which the court historians chose to call the Golden Age of Turkmenbashi. The sudden death of any autocratic head of state is fraught with serious political troubles and risks. This is especially true of the East. The outwardly closely knit Turkmenian society is torn apart by clan, regional, and………………